Existence of Technical Efficiency Level of Melon Farming with the Greenhouse System in East Java, Indonesia - Firmanda, Syauqi Agung; Hanani, Nuhfil; Asmara, Rosihan (Universitas Panji Sakti, 2025)
The problem of land conversion is a crucial issue for increasing melon productivity. Adoption of greenhouse technology as an alternative solution in increasing crop productivity. This study aimed to assess the technical efficiency of melon farming with a greenhouse system as an alternative technology that may increase melon productivity. The research was conducted in East Java on 60 samples of greenhouse melon farmers. The estimation of technical efficiency is determined using the Stochastic Frontier Translog approach. Production inputs of labor, seeds, and organic fertilizer have a positive elasticity to increase greenhouse melon production. While land area, Anorganic fertilizers, pesticides, and nutrients do not have a significant effect on increasing greenhouse melon production. Most melon farmers in East Java can utilize production inputs of greenhouse technology efficiently, although 26.67% of farmers need help to use production inputs rationally. Technical efficiency achieved by melon farmers who adopt greenhouse technology is determined by the number of family dependents, extension intensity, farmer group participation, and partnership relationships. The main employment status of melon farmers has a negative influence on increasing the technical efficiency of melon greenhouse farming. Regeneration of farmers and input subsidies in the form of organic fertilizers are essential to have a greater impact on melon farmers who apply greenhouse technology in the long term